Quantification of specific growth patterns and frequency of the empty sella phenomenon in growth hormone-secreting pituitary adenomas. Issue 104 (July 2018) - Bier, Georg; Hempel, Johann-Martin; Grimm, Florian; Ernemann, Ulrike; Bender, Benjamin; Honegger, Juergen
Highlights: The frequcency of an empty sella is increased in acromegaly patients. GH-secreting adenomas show a quantificable, downward-directed growth. Hypothetically, this growth pattern reflects speciric bone remodeling processes. Craniometric measures can be used for pituitary adenoma differentiation. Abstract: Purpose: To assess and quantify the prevalence and co-occurence of a sellar floor lowering and empty sella phenomenon in patients with GH (growth hormone)-secreting pituitary adenoma. Methods: A total number of 159 acromegalic patients were included in this study, as well as two control groups (150 patients with non-GH-secreting adenomas and 50 patients without pituitary adenomas). Magnetic resonance images of all patients were evaluated for presence of an empty sella, downward and lateral tumor extension, and maximum superoinferior diameter of the mass. Additionally, these values were correlated with growth hormone and IGF-1 levels. Results: The empty sella phenomenon was detected significantly more often in patients with a GH-secreting adenoma with a prevalence of 22% vs. 5.3% in non-GH-secreting adenomas (p < 0.001) or 8% in the healthy control group (p = .036). Moreover, GH-secreting adenomas presented with a significant rate of downward tumor extension (74.8% vs. 35.5%; p < 0.001), whose extent correlated inversely but weakly with the GH hormone level (r = − 0.17; p = .036). It was also found that a decreased superoinferior diameter and higher ratio of intrasellar to suprasellar extension are predictive quantitative values for the presence of a GH-secreting adenoma (area under curve, 0.712). Conclusions: GH-secreting pituitary adenomas are frequently associated with an empty sella phenomenon. Moreover, GH-secreting adenomas are frequently accompanied by an enhanced, quantitatively measurable impression of the sellar floor. Hypothetically, this is caused by tumor-induced local bone remodeling processes.